Application of UAV-based photogrammetry and normalised water index (NDWI) to estimate the rock mass rating (RMR): A case study. (October 2022) - Ismail, Afiqah; A Rashid, Ahmad Safuan; Sa'ari, Radzuan; Rasib, Abd Wahid; Mustaffar, Mushairry; Abdullah, Rini Asnida; Kassim, Azman; Mohd Yusof, Norbazlan; Abd Rahaman, Norisam; Mohd Apandi, Nazirah; Kalatehjari, Roohollah
Abstract: Rock Mass Rating (RMR) is an effective method in assessing rock stability conditions. Rock slope instability and failures can be attributed to various factors, including unfavourable slope geometries, the presence of water, geological discontinuities, weak or weathered slope materials, and extreme weather conditions. The main factor highlighted in this research is the presence of water and the weakening effect of the slope-water interaction. Traditionally, RMR is measured through the conventional method, and this parameter is determined by visual observation. However, this is of limited use if the study area is large and/or difficult to access. The digital remote sensing method proposed by the current study can overcome this limitation. This method uses two different compact remote sensors (RS) mounted within an Unmanned Aerial Vehicle (UAV), namely, a Red Green Blue (RGB) sensor, with a spectrum ranging from 0.4 μm to 0.7 μm, and Near-Infrared (NIR) sensor, with a spectrum ranging from 0.7 μm to 1.3 μm. The Normalised Difference Water Index (NDWI) algorithm is then used to generate the existence of water bodies on the rock surface and classify the water condition, following the RMR classification. The effectiveness and validity of the proposed method were proved by comparing the results of the NDWI method with a site survey; the classification of water conditions in RMR was aided by the digital remote sensing method. The water classification conditions are: < 0 = rate 15 (dry), 0.00–0.15 = rate 10 (damp), 0.16–0.25 = rate 7 (wet), and 0.26–0.40 = rate 4 (dripping). Highlights: Water infiltration frequently triggers rock slope instability and slope failure. Normalised Difference Water Index (NDWI) generates the existence of water bodies on the slope. Water indices are used to rate water conditions according to Slope Mass Rating (SMR). The higher the index value, the higher amount of water. NDWI value of less than zero represents the dry area.